2015
DOI: 10.1080/15228835.2014.1000558
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence Service Providers’ Needs and Perceptions of Technology: A Qualitative Study

Abstract: There is growing recognition of the need to better understand the intersections between the work of domestic violence service providers and technology. Professionals who work with clients impacted by domestic violence are increasingly using technologies across different aspects of their work, including communicating with other professionals and seeking information and resources via the Internet. The current study used qualitative data from two sources-individual interviews and two focus groups-to learn about d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…As opposed to previous findings that DV/SA organizations have been reluctant to integrate digital technologies into their organizational practices (Murray et al, 2015), DV/ SA organizations in this sample described using digital technologies in new and often unexpected ways. This study found that while organizations in this sample are understandably cautious and aware of the risks associated with the use of digital interventions, the external conditions present during the pandemic resulted in an accelerated use of existing digital technologies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…As opposed to previous findings that DV/SA organizations have been reluctant to integrate digital technologies into their organizational practices (Murray et al, 2015), DV/ SA organizations in this sample described using digital technologies in new and often unexpected ways. This study found that while organizations in this sample are understandably cautious and aware of the risks associated with the use of digital interventions, the external conditions present during the pandemic resulted in an accelerated use of existing digital technologies.…”
Section: Discussioncontrasting
confidence: 99%
“…Technological innovations include telehealth platforms, text lines, wearable devices, and web-based communication portals, which afford new platforms for practitioners to connect virtually with their clients. Prior research demonstrated that DV/SA staff are hesitant to use emerging technologies due to concerns over client confidentiality, safety issues, and limited technological competencies among staff (Murray et al, 2015). Given that individuals who perpetuate abuse are likely to use digital technologies as tools to coerce and surveil their current or former partners, these concerns are well-founded (Fiolet et al, 2021;Slakoff et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Domestic violence workers have expressed an interest in using safe technology that enhances their work efficiency and protects the confidentiality of their clients (Murray, Pow, Chow, Nemati, & White, 2015). The Safe Shelter Collaborative technology design, with the incorporation of the CEAT designed by service providers, meets those standards.…”
Section: Discussion and Implications For Practice And Future Researchmentioning
confidence: 99%
“…The findings from a qualitative study aimed at examining domestic violence service provider's needs and perceptions of using technology found that service providers have limited experience and knowledge about technological advances which resulted in them feeling anxious and uncertain about their abilities to use and learn new technological advances. Therefore, ongoing ICT related training and support needs to be provided to social workers for them to be able to effectively address technology-related concerns and questions that may arise in therapy for their clients and themselves (Murray, Nemati, White, Chow, & Pow, 2015). This article provides a survey, comparison, and classification of the existing cell phone-based violence prevention/intervention applications (apps).…”
mentioning
confidence: 99%